Surface modification vs sorption strength: study of nedaplatin drug supported on silica - Noseda Grau, Emilia (2019)
The interaction of nedaplatin drug with modified SiO2 (0 0 1) surfaces has been investigated within the framework of Density Functional Theory. Nedaplatin molecule is adsorbed spontaneously onto silica surfaces. Silica surface prevents drug degradation allowing the chemical attachment without any impact on the drug structure itself. The nedaplatin sorption is mainly governed by H-bonding interactions on hydrated and trimethylsilanefunctionalized surfaces, while the drug is major stabilized by NeO, OeO interactions and H partial dissociation on dehydrated silica. The differences on the adsorption strength could be used in future studies to control the drug release, developing delivery silica systems according therapy requirements.